A prospective study on tryptophan immunoadsorption in AQP4 antibody‐positive neuromyelitis optica spectrum disorders. Issue 3 (1st February 2022) - Liu, Jing; Zhou, Ran; Gong, Yong; Ding, Xia; Huang, Qi; Zhang, Yin; Feng, Yiduo; Wang, Dongxue; Zhou, Heng; Ma, Yuetao; Zhang, Xinghu; Zhou, Yilun
Abstract: Introduction: Neuromyelitis optica spectrum disorders (NMOSD) is a rare inflammatory demyelinating disease of the central nervous system. NMOSD pathogenesis is mainly mediated by antibodies directed against aquaporin4 (AQP4 antibody). Immunoadsorption (IA) could specifically remove pathogenic antibody to alleviate the disease. Until now, prospective studies concerning the efficacy of IA on NMOSD are scarce. This study aims to prospectively evaluate the efficacy and safety of IA in the treatment of NMOSD. Patients and Methods: We included patients with AQP4 antibody‐positive NMOSD who were hospitalized from September 2019 to September 2020, with no significant improvement in symptoms after 1 week of high‐dose intravenous steroid therapy. Tryptophan IA therapy was initiated with five sessions on alternate days. Expanded Disability Status Scale (EDSS), visual acuity, and laboratory values were measured before and after IA, with a follow‐up of 6 months. Spinal magnetic resonance imaging (MRI) characteristics were collected. Related side effects were recorded. Results: Seven patients were enrolled in the present study. After five IA, the patients' EDSS decreased from 5.71 ± 2.04 to 4.64 ± 2.29, P  = .006. The visual acuity of the three visually impaired patients was improved. AQP4‐IgG decreased significantly from 80.00 (interquartile range [IQR], 21.00‐80.00) (U/mL) to 9.72 (IQR, 5.21‐55.57) (U/mL) ( P  = .018). MRI of the spinal cord showed the scope of the myelopathy was narrowed and no significant enhancement was observed on postcontrast T1‐weighted image at 90 days after treatment. Only one patient had transient hypotension. Conclusions: Tryptophan IA therapy effectively and safely improved neurological function and visual acuity, and reduced the AQP4 antibody concentration in patients with NMOSD.